A Profile of eHealth Behaviors in China: Results From a National Survey Show a Low of Usage and Significant Digital Divide - Y. Alicia Hong; Zi Zhou (Frontiers Media S.A., 2018)
Background: The widely accessible Internet has boosted an enthusiasm for eHealth in China, but we know little about eHealth behaviors in the general population.Objective: To assess the prevalence of eHealth behaviors in general Chinese population and identify the predictors of digital divide.Methods: A nationally representative survey was administered in 2016-2017 with a sample size of 4,043. Five eHealth behaviors were assessed: search health information, communicate with healthcare providers, connect with patients of similar health conditions, buy medicine, and make doctor's appointment online. Multivariate logistic regression was employed to assess the independent relationship between eHealth behaviors and key demographic variables.Results: About 33% of participants have ever searched health information online, and the prevalence of other eHealth behaviors was less than 10%. The adoption of eHealth behaviors was significantly associated with younger age, more education, higher income, and urban residence. By contrast, gender, employment status, health insurance, and health status were not associated with eHealth behavior.Conclusion: The adoption of eHealth behaviors in the general Chinese population was low, and a significant digital divide exists. We caution against the speedy development of Internet hospitals and call for more resources allocated to bridge digital health divide.